Earthquake and wind load effects on existing RC minarets in north Cyprus - ReÅŸatoÄŸlu, Rifat; Mirata, TunÃ§; Karaker, Louay (International Journal of Engineering and Technology, 2018)
Minarets are tall and slender structures and are vulnerable to fail or get damaged under lateral loads. In recent years, the number of rein-forced concrete (RC) minarets in North Cyprus has increased significantly. Owing absence of structural code about how to design minarets, forced us to revise our knowledge about these structures. Door openings, geometry changes in the cross-sectional size and additional mass at balconies are one of the most frequently encountered problems in these unique structures. The main purpose is to make a comparison and discuss the results of wind and earthquake analysis of selected RC minarets according to ACI307-98, TEC2007 and TS498, in order to clarify weaknesses and critical points. For this reason four RC minarets of different heights which exist in North Cyprus have been mod-elled by using SAP2000, v19.0 package program. Two types of analysis adopted; static wind analysis and dynamic earthquake response spectrum analysis. The major findings of this study indicate that the dynamic elastic response spectrum analysis according to ACI307-98 is forming the major lateral design load for the RC minarets and an additional concern should be given for the crucial points in order to pre-serve ductility of these structures.